Low Maternal Seafood Intake During Exclusive Lactation Does Not Significantly Affect Milk Protein Content - Sari, Ratna Nurmalita; Nuramaliyah, Nuramaliyah (Journal of Applied Agricultural Science and Technology, 2025)
Human milk, which contains complex and highly variably biofluid that nourishes and protects the newborn, is the gold standard for infant nutrition. The biological activity of human milk is significantly influenced by proteins. However, the relationship between crude protein in human milk and the amount of milk consumed by mothers during the exclusive breastfeeding period has not been thoroughly investigated. In the current study, 194 healthy women who were exclusively breastfeeding participated in a cross-sectional study to collect human milk samples and complete a quantitative frequent food questionnaire (FFQ). The consumption of cereals, potatoes, sweet potatoes, leafy vegetables, fruits, other vegetables, legumes, nuts, eggs, meats, dairy products, and seafood was grouped based on the consumption of the mother the day before milk collection. The mid-infrared milk analyzer was used to analyze the samples and determine protein concentration. Using the t-test to analyze the impact of partial factors, and the F-test was employed to evaluate the influence of variables concurrently, at a 5% significance level. The statistical relationship between maternal diet and protein content was evaluated. Seafood consumption was categorized as low compared to other groups. Self-imposed maternal food restrictions may be the cause of the reduced seafood consumption. Human milk has an average protein level of 1.02 g/100 ml. According to the statistics, there was no significant correlation between the crude protein content of human milk and seafood consumption. However, a strong correlation was found between the consumption of eggs, legumes, and nuts, suggesting that these foods may impact on the protein content of human milk (p value <0.05). This finding would suggest that to improve the protein content composition of human milk, nursing mothers should consume more local, high-protein foods.